Deleterious Oral Habits Among School Going Children: A Cross Sectional Study - Amna Amir, Sadhna, Saba Parveen Soomro, Syed Hammad Ali Zaidi, Qasim Khalid, Zobia Nissa, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: This cross-sectional study aimed to determine the prevalence of deleterious oral habits among school-going children in Punjab, Pakistan. Methods: The study was conducted at Punjab Dental Hospital, Lahore, from July 2018 to July 2019. A total of 500 school-going children aged 6 to 12 years were included in the study. A structured questionnaire was used to collect demographic information and data on deleterious oral habits, including nail biting, thumb sucking, mouth breathing, lip biting, and tongue thrusting. The data were analyzed using SPSS version 22. Results: The prevalence of deleterious oral habits among school-going children in Punjab was found to be 72.6%, with nail biting being the most prevalent habit observed (48.2%), followed by thumb sucking (17.4%), mouth breathing (12.4%), lip biting (9.4%), and tongue thrusting (5.2%). There was a significant association between the prevalence of deleterious oral habits and demographic variables such as gender, age, and family income and education level of parents. Conclusion: The high prevalence of deleterious oral habits among school-going children in Punjab, Pakistan, is a public health concern that requires attention and intervention to promote oral health and prevent the adverse effects of these habits on oral and general health. Early intervention and education programs should be implemented to promote oral health and prevent deleterious oral habits among children. Our study also provides valuable information for policymakers to develop targeted interventions to address oral health issues among children from different socioeconomic backgrounds. Keywords: Deleterious oral habits, children